Study of the Role of Vortex Displacement in Contact Loading of Strengthening Coatings Based on Movable Cellular Automaton Modeling; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Smolin A. Yu. Alexey; Eremina G. M. Galina; Shilko E. V. Evgeny; Psakhie S. G. Sergey Grigorievich (2015, 2015)
Title screen